KAJIAN PUPUK KOTORAN SAPI DAN PERDEDAAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) - Roosenani, Arifah; Susanti, Ambar; Kurniawan, Dwi Wahyu (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2020)
The purpose of the research, to determine the effect of cow manure and urea fertilizer on the growth and production of sweet corn (Zea mays saccharata Sturt). The research was carried out in Tambar Village, Jogoroto District, Jombang Regency, from December 2017 to February 2018. The research method was carried out using a 2 X 3 factorial experiment arranged in a completely randomized design. the results of the study were analyzed using variance at 5% level. If there is a real difference then the LSD test at the level of 5% if it is significantly different. The first factor is the use of organic fertilizer consisting of 2 levels / levels, namely: K0: Without cow manure, K1: with cow manure with a dose of 3 tons / ha = 333.3 grams / plant, the second factor is inorganic fertilizer which is divided into 3 level / level, namely: P1: Urea fertilizer 5 kg / ha = 0.833 gram / plant P2: Urea fertilizer 15 kg / ha = 2.5 gram / plant P3: Urea fertilizer 25 kg / ha = 4.2 gram / plant. The results of observations of cow manure and urea fertilizer showed no significant effect on plant height, number of leaves, stems, and wet weight of cob cobs.